Banking expectations: the promises and problems of biobanks. (November 2007) - Tutton, Richard
In the last decade, governments, medical charities, pharmaceutical companies and disease advocacy organizations have spent considerable time and money developing biobanks to aid drug discovery and the investigation of disease. This article identifies and assesses the various expectations that have driven the investment in different types of biobanks. It suggests that they have been the focus of unrealistic promises about producing a ''biobank revolution'' that will transform biomedicine and healthcare. We need more modest expectations about what can be achieved, and need to tackle certain conceptual and methodological challenges for biobanks to fulfill their potential.